2017
DOI: 10.1002/14651858.cd012252.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Clinician-targeted interventions to influence antibiotic prescribing behaviour for acute respiratory infections in primary care: an overview of systematic reviews

Abstract: We found evidence that CRP testing, shared decision making, and procalcitonin-guided management reduce antibiotic prescribing for patients with ARIs in primary care. These interventions may therefore reduce overall antibiotic consumption and consequently antibiotic resistance. There do not appear to be negative effects of these interventions on the outcomes of patient satisfaction and reconsultation, although there was limited measurement of these outcomes in the trials. This should be rectified in future tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(161 citation statements)
references
References 74 publications
7
150
0
Order By: Relevance
“…Systematic review evidence suggests that shared decision-making reduces prescribing (48) . CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Main Findings In Comparison With Previous Researchmentioning
confidence: 99%
“…Systematic review evidence suggests that shared decision-making reduces prescribing (48) . CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Main Findings In Comparison With Previous Researchmentioning
confidence: 99%
“…The best evidence is for communication skills training, point-of-care diagnostics and peer-comparison feedback. 31,[34][35][36][37] However, multifaceted strategies targeting both the general public and the prescriber are likely to optimize the impact of community antimicrobial stewardship programs. 38 This study supports the need for a province-wide evidence-based antimicrobial stewardship program, with a strong surveillance component, to improve the appropriate use of outpatient antibiotics and slow the emergence of drug-resistant infections.…”
Section: Openmentioning
confidence: 99%
“…6 A recent Cochrane umbrella review of cliniciantargeted interventions to influence antibiotic prescribing concluded that CRP is one of three effective strategies, along with shared decision making and procalcitonin-guided management. 7 However, the latter was only studied in two trials, and in the largest general practice diagnostic study aiming to develop a clinical rule for pneumonia in 3106 patients with cough, procalcitonin did not add any diagnostic information. However, in the same study CRP at the optimal cut-off of 30 mg/L improved the accuracy of a clinical rule based on signs and symptoms.…”
Section: The Impact Of Crp On Antibiotic Prescribing Decisionsmentioning
confidence: 99%